Sosialisasi Pembuatan Linktree sebagai Media Pembelajaran Alternatif Masa Pandemi Covid 19 pada Guru-Guru SDN 18 Galung Lombok Polewali Mandar - Nur Amaliah; Jirana Jirana; Mesra Damayanti (Dewan Pimpinan Daerah (DPD) Perkumpulan Dosen Indonesia Semesta (DIS) Jawa Timur, 2021)
The covid-19 pandemic has changed the learning paradigm from face-to-face to online. The learning that takes place online needs the application of creative learning media, such as Linktree. Linktree is a tool that can be used to unite lesson plans, materials, quizzes, and other learning tools in the from of links. Learning media such as linktree are urgently needed at SDN 018 Galung Lombok, Polewali Mandar as one of the schools that affected by the pandemic. The devotion method is carried out by providing socialization related to the use of the Linktree application which is an alternative media in learning during the pandemic. The result of this devotion is that SDN 018 Galung Lombok teachers have an awareness of the importance of using learning media and gain knowledge about Linktree learning media.